Combined assessment using optical colonoscopy and computed tomographic colonography improves the determination of tumor location and invasion depth. Issue 1 (21st September 2016) - Kanazawa, Hidenori; Utano, Kenichi; Kijima, Shigeyoshi; Sasaki, Takahiro; Miyakura, Yasuyuki; Horie, Hisanaga; Lefor, Alan Kawarai; Sugimoto, Hideharu
Abstract: Introduction: An accurate assessment of the depth of tumor invasion in patients with colon cancer is an important part of the preoperative evaluation. Whether computed tomographic colonography (CTC) or optical colonoscopy (OC) is better to accurately determine tumor location and invasion depth has not been definitively determined. The aim of this study was to determine the diagnostic accuracy of tumor localization and tumor invasion depth of colon cancer by preoperative OC alone or combined with CTC. Methods: Study participants include 143 patients who underwent both preoperative CTC using automated CO2 insufflation and OC from July 2012 to August 2013. Results: The accuracy of tumor localization was significantly better with CTC than with OC (OC, 90%; CTC, 98%; P < 0.05). No tumor in the descending colon was localized accurately via OC alone. The accuracy of tumor invasion depth was better with CTC plus OC than with OC alone (OC, 55%; CTC, 73%; P < 0.05). Conclusions: OC combined with CTC provides a more accurate preoperative determination of tumor localization and invasion depth than OC alone.